A Legal History of the New Zealand Jury Service - Introduction, Evolution, and Equality? - Powles, Michèle (Victoria University of Wellington Law Review, 1999)
This article traces the development of the New Zealand jury system. Most noteworthy in this development has been the lack of controversy the system has created. At the end of the nineteenth century, however, the pursuit of equality in the legal system generally led to debate and reform of juries in relation to representation, race and gender.